Entrepreneurial Intentions of Teams: Sub-Dimensions of Machiavellianism Interact With Team Resilience - Schippers, Michaéla C.; Rauch, Andreas; Belschak, Frank D.; Hulsink, Willem (Frontiers in Psychology, 2019)
Machiavellians are often seen as manipulative people who contribute negatively to teams and ventures. However, recent work has shown that Machiavellians can also cooperate and act in pro-social ways in a team context. Thus, some aspects of Machiavellianism might be conducive for teams and team members’ intentions to start a business venture. Most studies in this area have failed to (a) assess the effect of Machiavellianism at the team level, (b) take into account the dimensional nature of Machiavellianism, and (c) assess moderators of these effects. We propose that the combination of Machiavellianism and resilience in teams predict team entrepreneurial intentions (EI). Moreover, we propose that different team level dimensions of Machiavellianism (amoral manipulation, desire for status, desire for control, distrust of others) are differentially related to EI. More specifically, we expect at the team level that amoral manipulation and desire for status are positively related to changes in EI (as teams high on these dimensions feel that they can use unethical practices that give them an advantage in being successful), whereas desire for control and distrust of others should be negatively related to changes in EI (as entrepreneurial teams usually work in less structured situations and need to closely work together). Furthermore, all sub-dimensions of Machiavellianism should interact positively with team resilience as resilience acts as a buffer that protects teams from potential negative effects of Machiavellianism. In a multi-wave study among newly formed teams engaged in entrepreneurship projects, controlling for psychopathy and narcissism, we found partial support for our hypotheses. Results supported our expectations for the “amoral manipulation” and “desire for control” sub-dimensions, but not for the “desire for status” and the “distrust of others” sub-dimensions of Machiavellianism, with distrust of others showing unexpectedly opposite effects. This study contributes to the literature by looking at the dimensions of Machiavellianism at the level of entrepreneurial teams in conjunction with the more positive team characteristic, resilience. Our results indicate that the relationship between Machiavellianism and EI is more complex than previously hypothesized, as the sub-dimensions are sometimes positively and sometimes negatively related to entrepreneurial intentions and interact with team-level resilience